Pemanfaatan Jagung Manis Dan Kulit Buah Naga Untuk Olahan Mie Kering Kaya Nutrisi - Analianasari, Analianasari; Zaini, Muhammad (Politeknik Negeri Lampung., 2016)
The research was aimmed at studying (1) Determine the percentage of wheat flour,sweet corn and skin dragon fruit right in the manufacture of dry noodles that can beaccepted by consumers, and (2) Determine the influence of addition of sweet corn andrind of a dragon on the content of moisture, ash, protein, and preferences ofconsumers towards the parameters of color, flavor, elasticity, and sensory overall.The method used in this study is a factorial experimental design with two factors,namely the substitution treatment of sweet corn pasta and red dragon fruit skinextracts of the flour. Substitution of sweet corn used is 10%, 20% and 30%. Mediumaddition of dragon fruit peel extract of 5%, 10% and 15%. Each experiment carriedrepeat 3 times, so it will be acquired unit (unit) trial were 9 units trial. The dataobtained were tested with the test Barlett diversity and additional data with Tuckeytest. Furthermore, to see the value of the middle test treatment Significant Difference(LSD) at 5% level. The resulting dried noodles then analyzed the water content, ashprotein, the overall sensory test. Results from the study if seen from the test sensorypreferences overall, generally panelists prefer the treatment of sweet corn and dragonfruit with a concentration of 20%, 15% better than the taste, color and elasticity ofnoodles, while from the nutritional content of dried noodles sweet corn and dragonfruit SNI is in conformity with dry noodles.Keywords: Sweet corn, dragon fruit peel, dried noodles